Spatially differentiated nitrogen supply is key in a global food–fertilizer price crisis - Snapp, Sieglinde S.; Sapkota, Tek Bahadur; Chamberlin, Jordan; Cox, Cindy M.; Gameda, Samuel; Jat, Mangi Lal; Marenya, Paswel Phiri; Mottaleb, Khondoker Abdul; Negra, Christine; Senthilkumar, Kalimuthu; Sida, Tesfaye Shiferaw; Singh, Upendra; et al. (Springer, 2023)
A regional geopolitical conflict and sudden massive supply disruptions have revealed vulnerabilities in our global fuel–fertilizer–food nexus. As nitrogen (N) fertilizer price spikes threaten food security, differentiated responses are required to maintain staple cereal yields across over- and underfertilized agricultural systems. Through integrated management of organic and inorganic N sources in high- to low-input cereal production systems, we estimate potential total N-fertilizer savings of 11% in India, 49% in Ethiopia and 44% in Malawi. Shifting to more cost-effective, high-N fertilizer (such as urea), combined with compost and integration of legumes, can optimize N in N-deficient systems. Better targeted and more efficient N-fertilizer use will benefit systems with surplus N. Geospatially differentiated fertilization strategies should prioritize high-N fertilizer supply to low-yield, N-deficient locations and balanced fertilization of N, P, K and micronutrients in high-yield systems. Nationally, governments can invest in extension and realign subsidies to enable and incentivize improved N management at the farm level.